Effects of zinc deficiency on rice growth and genetic factors contributing to tolerance - Wissuwa, Matthias; Ismail, Abdelbagi M.; Yanagihara, Seiji (Oxford University Press, 2006)
Zinc (Zn) deficiency is the most widespread micronutrient disorder in rice (Oryza sativa), but efforts to develop cultivars with improved tolerance have been hampered by insufficient understanding of genetic factors contributing to tolerance. The objective of this paper was to examine alternative evaluation methods and to identify the most informative traits that would provide realistic information for rice breeders and to map quantitative trait loci (QTLs) associated with tolerance. Screening experiments in low-Zn nutrient solution and in a Zn-deficient field did not produce similar tolerance rankings in a set of segregating lines, which suggested that rhizosphere effects were of greater importance for lowland rice than internal Zn efficiency. The most severe symptom in the field was high plant mortality. The occurrence of leaf bronzing, usually regarded as indicative of susceptibility, did not necessarily concur with high plant mortality, which implied that both were under independent genetic control. The QTL mapping experiment conducted in the field with a population derived from a cross of IR74 (intolerant) with Jalmagna (tolerant) largely confirmed this. Four QTLs associated with plant mortality were detected, and only one of those colocalized with one of the four QTLs detected for leaf bronzing. The two most influential QTLs for plant mortality were detected on chromosomes 2 and 12. They explained 16.6% and 24.2% of the variation, and alleles of the tolerant donor parent Jalmagna reduced mortality by 16.6% and 14.8%, respectively. QTLs for plant mortality acted in a purely additive manner, whereas digenic epistatic interactions were important for leaf bronzing.